Introduction to dossier. Citizenships and sexualities in Latin America - Lind, Amy; Argüello Pazmiño, Sofía (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2009)
Introduction to dossier. Citizenships and sexualities in Latin America